Evaluation of Augmented Reality Technology in the English Language Field - Silva, Manoela; Roberto, Rafael; Teichrieb, Veronica (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2015)
Augmented Reality (AR) is heralded to be a promising technology for education. Therefore, it is important to properly evaluate it so practitioners feel more confident in its use. The aims of this study are threefold: (a) to evaluate the use of an AR tool for young children, in the English teaching field concerning linguistic concepts and competencies; (b) to discuss possibilities of use for AR tools in the classroom environment as well as reflect about the potential and difficulties involved in their introduction, and (c) to provide guidelines in order to assist researchers when conducting similar evaluations. The evaluation considered multiple metrics and involved the teacher as an instructional designer. Results supported the hypothesis that AR may help students in the learning process.